Strategi pengembangan lembaga pendidikan taman kanak-kanak - Akbar Pandu Dwinugraha (Universitas Merdeka Malang, 2021)
This study tries to provide a development strategy for kindergarten educational institutions. This strategy can later be used by local governments in developing kindergarten educational institutions in their respective regions. This study uses a combination research type with a survey method and will analyze three aspects including the management and implementation of kindergartens; aspects of the quality of educators and teaching staff; and aspects of the availability of basic equipment, facilities and infrastructure. The research location is the administrative area of ​​Blitar City, East Java Province with data collection time from March to June 2019. Field data were collected using questionnaires, interviews, documentation and focus group discussions. Based on existing conditions, which have been analyzed based on internal and external factors, three strategic recommendations have been produced which include (1) Assistance in budgeting and monitoring the use of BOP funds (Operational Assistance for Early Childhood Education); (2) Increasing the cooperative relationship of kindergarten institutions through sponsorship schemes, (3) Standardization of minimal facilities and infrastructure as an effort to reduce the imbalance in the availability of facilities and infrastructure in kindergarten institutions in Blitar City.